Cerrado cashew (Anacardium othonianum Rizz) apple pomace: chemical characterization and optimization of enzyme-assisted extraction of phenolic compounds - FREITAS, Bheatriz Silva Morais de; HAAS, Isabel Cristina da Silva; PEREIRA-COELHO, Marina; ALMEIDA, Adrielle Borges de; ALMEIDA, Júlia dos Santos Opuski de; EGEA, Mariana Buranelo; SILVA, Fabiano Guimarães da; PETKOWICZ, Carmen Lucia de Oliveira; FRANCISCO, Alicia de; MADUREIRA, Luiz Augusto dos Santos; FREIRE, Carlise Beddin Fritzen; AMBONI, Renata Dias de Mello Castanho (Food Science and Technology, 2023)
Cerrado cashew (Anacardium othonianum Rizz) pomace is the main by-product from the processing of cashew apples. This study aimed to (i) investigate the difference between the chemical compositions of the pomaces of yellow (YCP), orange (OCP), and red (RCP) cashew apples based on their mineral, monosaccharide, and polyphenolic compositions; and (ii) optimize enzyme-assisted extraction of the phenolic compounds from Cerrado cashew apple pomace. Potassium and iron were the main macro- and microelements found in residue, and significant differences were noted in the profiles of the samples. The predominant monosaccharides in the samples included glucose (52.7–60.6 mol%) and uronic acid (12.5–14.5% mol). The complete three-level factorial design allowed the optimization of pH, extraction time, and temperature, leading to an optimal extraction of polyphenols at pH 5.5, an extraction time of 120 min, and a temperature of 55°C. Myricetin (43.03–44.26 mg/kg), vanillic acid (30.96–32.32 mg/kg), and gallic acid (11.34–29.25 mg/kg) were the major polyphenols found in the samples. These results confirmed that regardless of the color of Cerrado cashew apple pomace, this by-product is a potential source of phytochemicals for application in sustainable and functional food products.